Rivolte urbane e rivolte contadine nell'Europa del Trecento - Bourin, Monique (Biblioteca di storia, 2008)
The book contains the proceedings of the international conference held in Florence in the spring of 2005. It addresses the subject of the urban and rural revolts of the 14th century, which had recently undergone a period of neglect following the enormous popularity it enjoyed during the 1960s and 70s in the wake of the tormented events of those decades. The sixteen essays comprised in the book, contributed by specialists from five different European countries, develop three different forms of analysis constructed within the timeframe of a broadly-conceived fourteenth century, based on a consolidated and shared chronology, extending from the last decades of the thirteenth up to the early decades of the fifteenth.